Relationship between 12–16-Year-Old Athletes’ Self-Esteem, Self-Confidence and Bullying (Baltic Journal of Sport and Health Sciences, 2012)
Research  background  and  hypothesis.  Previous  research  has  proved  that  children  engaged  in  sports  easier integrate into the society and their psychological well-being is much higher,  sports activities can help them resist to the harmful influence of their peers and prevent them from engaging into delinquent behavior. However, there still is a lack of a studies providing evidence about factors that determine the expression of compulsion. Hypothesis: The level of self-esteem and self-confidence of adolescent athletes influences the occurrence of bullying and the initiation of it.  Research  aim  was  to  disclose  the  relationship  between  the  level  of  adolescent  athletes’  self-esteem,  self-confidence and the occurrence of bullying.Research methods. The study applied I. Shostrom’s modified self-esteem scale questionnaire and the adapted Bullying Scale for Schoolchildren. Research  results.  Results  showed  a  weak  correlation  between  bullying  and  self-esteem  levels  (γ =  0.24; p > 0.05). We found a weak adverse relationship between initiating bullying and self-assessment levels (γ = –0.16; p > 0.05), weak adverse correlation between experienced bullying and self-confidence levels (γ = –0.15; p > 0.05) and a weak linear relationship between initiating bullying and self-confidence (γ = 0.20; p > 0.05).Discussion and conclusions. Contrary to what we expected, we observed that athlete adolescents with the high levels of self-esteem suffered from bullying sometimes and often. Research findings suggest that adolescents who tend to initiate bullying demonstrated moderate and low levels of self-esteem. Most of athlete adolescents admitted that that did not initiate bullying or if they did, that was done only occasionally. It was found that adolescents with high and moderate self-confidence levels experienced bullying occasionally or not at all. Some athletes with low self-confidence levels professed that they suffered from bullying more often, and they also admitted that they often initiated bullying themselves. In our research we were unable failed to provide evidence which would prove that sports activities impacted or influenced adolescents’ bullying initiatives or experiences; therefore further research is needed to determine whether self-esteem and other internal personality qualities could affect the expression of bullying among non-athlete adolescents.Keywords: aggression, adolescents’ self- assessment, self-confidence.